Restaging transurethral resection in ta high-grade nonmuscle invasive bladder cancer: a systematic review. Issue 1 (January 2022) - Regnier, Sophie; Califano, Gianluigi; Elalouf, Vincent; Albisinni, Simone; Aziz, Atiqullah; Di Trapani, Ettore; Krajewski, Wojciech; Mari, Andrea; D'Andrea, David; Pradère, Benjamin; Soria, Francesco; Afferi, Luca; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: The role of a re-transurethral resection (TUR) is clearly demonstrated in T1 high-grade nonmuscle invasive bladder cancer. However, its role remains controversial for Ta high-risk tumors and the recent European guidelines stated that the second look procedure could be avoided for these patients despite harboring a high-risk of both disease recurrence and progression. We aimed to evaluate the added benefit on staging, response to bacillus Calmette–Guérin and oncological outcomes of re-TUR in patients with Ta high-grade nonmuscle invasive bladder cancer. Recent findings: Overall, we identified 15 studies, including 3912 patients from which 743 harbored Ta high-grade disease. Delay between first and second TUR was ranging from 2 to 12 weeks (median 5.6 weeks). The rate of residual disease was 52.8% (range 17–67%). The rate of overall upstaging to T1 and muscle-invasive disease were 10.9 and 4.7%, respectively. Although there was a trend toward improvement of recurrence-free survival outcomes, no definitive conclusions can be drawn due to the retrospective design of the studies included. Summary: Residual tumor is common after initial TUR for Ta high-grade. Re-TUR is useful in reducing the rates of residual disease, may improve staging, response to bacillus Calmette–Guérin and oncological outcomes.